Mycelial abundance and other factors related to truffle productivity in Tuber melanosporum–Quercus ilex orchards - Suz, Laura M.; Martín, María P.; Oliach, Daniel; Fischer, Christine R.; Colinas, Carlos (FEMS Microbiology Letters, 2008)
Relative quantification of DNA from Tuber melanosporum mycelia was performed by conventional and real-time PCR in soil from trees in three truffle orchards of different ages to determine: (1) whether burn appearance is related to the amount of T. melanosporum mycelium in soil, and (2) whether productivity onset and truffle production are related to (a) the amount of T. melanosporum mycelium in soil, (b) tree height and diameter, (c) burn extension and (d) surface rock cover. The burn seems to appear only after a certain amount of mycelium has formed. Precociously productive trees presented higher quantities of mycelium than nonproductive trees in the productivity onset study, while highly productive trees presented less quantities of mycelium than nonproductive trees in the productivity study. Trees with high but not excessive surface rock cover showed greater truffle production. Larger trees tended to display a burn earlier than smaller trees.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: burn; DNA soil mycelium; real-time PCR; rock cover; truffle; Tuber melanosporum

Mycelial abundance and other factors related to truffle productivity in Tuber melanosporum–Quercus ilex orchards (FEMS Microbiology Letters, 2008)
Relative quantification of DNA from Tuber melanosporum mycelia was performed by conventional and real-time PCR in soil from trees in three truffle orchards of different ages to determine: (1) whether burn appearance is related to the amount of T. melanosporum mycelium in soil, and (2) whether productivity onset and truffle production are related to (a) the amount of T. melanosporum mycelium in soil, (b) tree height and diameter, (c) burn extension and (d) surface rock cover. The burn seems to appear only after a certain amount of mycelium has formed. Precociously productive trees presented higher quantities of mycelium than nonproductive trees in the productivity onset study, while highly productive trees presented less quantities of mycelium than nonproductive trees in the productivity study. Trees with high but not excessive surface rock cover showed greater truffle production. Larger trees tended to display a burn earlier than smaller trees.